Multidisciplinary management in chronic myeloid leukemia improves cardiovascular risk measured by SCORE - Blanco Sánchez, Alberto; Gil Manso, Rodrigo; Carreño-Tarragona, Gonzalo; Paredes Ruiz, Diana; González Olmedo, Jesús; Martínez-López, Joaquín; Díaz Pedroche, Carmen; Ayala, Rosa (Frontiers in Pharmacology, 2023)
Introduction: Cardiovascular events are one of the main long-term complications in patients with chronic myeloid leukemia (CML) receiving treatment with tyrosine kinase inhibitors (TKIs). The proper choice of TKI and the strict care of risk factors can reduce cardiovascular comorbidity in this population. Methods: This study evaluated the cardiovascular risk of a cohort of patients with CML at diagnosis and after follow-up in a specialized cardiovascular risk consultation. To do this, we analyzed data from 35 patients who received TKIs and were referred to the aforementioned consultation between 2015 and 2018 at our center. Cardiovascular risk factors were analyzed separately, as well as integrated into the cardiovascular SCORE, both at diagnosis and at the last visit to the specialized consultation. Results: At the time of diagnosis, 60% had some type of risk factor, 20% had a high or very high risk SCORE, 40% had an intermediate risk, and 40% belonged to the low risk category. The main cardiovascular adverse event developed during follow-up was hypertension (diagnosed in 8 patients, 23%). 66% of patients quitted smoking, achieving control of blood pressure in 96%, diabetes in 75%, weight in 76%, and dyslipidemia in 92%. 5.7% of patients suffered a thrombotic event and a significant percentage of patients showed a reduction in their SCORE. Conclusion: Our study shows the benefit of follow-up in a specialized consultation of patients with CML treated with TKI through the control of cardiovascular risk factors.